The Protected Areas network may be insufficient to protect bird diversity in a fragmented tropical hotspot under different climate scenarios - Tonetti, Vinicius [UNESP]; Bocalini, Fernanda; Schunck, Fabio; Vancine, Maurício Humberto [UNESP]; Butti, Mariella; Ribeiro, Milton [UNESP]; Pizo, Marco [UNESP] (Elsevier, 2024)
We identified the 30% most-important forest remnants for conservation in the Atlantic Forest domain in South America based on three bird diversity components: (1) overall species potential distribution, (2) potential distribution of threatened species, and (3) diversity of functional traits. We evaluated the extent of overlap among priority areas using the different approaches and analysed the efficiency of the current Protected Areas network at protecting biodiversity in current and potential future (2040 and 2080) climate scenarios. The overlap among the most important areas is low among the different bird diversity components in all climate scenarios, and few changes were found in priority areas between the current and future scenario. The proportion of species that reached the minimum amount of their distribution areas protected varied from zero to 4% depending on the climate scenario and the species conservation status (threatened or not). Priority areas based on the potential distribution of threatened species were less correlated to areas based on the overall species potential distribution than to functional traits in all climate scenarios, suggesting that there might be considerable differences between species composition and their functionalities. Our analyses point out the main regions where resources should be allocated to conservation of birds in a mega-biodiversity region.
Keywords: Atlantic Forest; Birds; Climate crisis; Functional traits; Landscape ecology; Species distribution models; Zonation